Research among Copycats: R&D, Spillovers, and Feedback Strategies - Grega Smrkolj; Florian Wagener (Tinbergen Institute, 2014)
We study a stochastic dynamic game of process innovation in which firms can initiate and terminate R&D efforts and production at different times. We discern the impact of knowledge spillovers on the investments in existing markets, as well as on the likely structure of newly forming markets, for all possible asymmetries between firms. We show that the relation between spillovers, R&D efforts, and surpluses is non-monotonic and dependent on both the relative and absolute efficiency of firms. Larger spillovers increase the likelihood that a new technology is brought to production, but they do not necessarily make the industry more competitive.
Keywords: C61; C63; C73; D43; D92; L13; O31; 330; Differential game; Feedback Nash equilibrium; Numerical partial differential equations; R&D; Spillovers